2020
DOI: 10.1001/jamaoncol.2020.0237
|View full text |Cite|
|
Sign up to set email alerts
|

Durvalumab With or Without Tremelimumab vs Standard Chemotherapy in First-line Treatment of Metastatic Non–Small Cell Lung Cancer

Abstract: IMPORTANCECheckpoint inhibitors targeting programmed cell death 1 or its ligand (PD-L1) as monotherapies or in combination with anti-cytotoxic T-lymphocyte-associated antigen 4 have shown clinical activity in patients with metastatic non-small cell lung cancer.OBJECTIVE To compare durvalumab, with or without tremelimumab, with chemotherapy as a first-line treatment for patients with metastatic non-small cell lung cancer. DESIGN, SETTING, AND PARTICIPANTSThis open-label, phase 3 randomized clinical trial (MYSTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
397
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(460 citation statements)
references
References 47 publications
8
397
0
6
Order By: Relevance
“…Blood based cfDNA offers a more convenient approach to assess TMB and potentially overcome the problem of tumor heterogeneity, but fewer clinical studies have validated this approach. In the B-F1RST and MYSTIC trials, blood-based TMB predicted response to immune checkpoint inhibitors in the first-line treatment of NSCLC (13,14). However, the relationship between TMB scores in tissue and blood remains unclear.…”
Section: What Is Tmb?mentioning
confidence: 99%
“…Blood based cfDNA offers a more convenient approach to assess TMB and potentially overcome the problem of tumor heterogeneity, but fewer clinical studies have validated this approach. In the B-F1RST and MYSTIC trials, blood-based TMB predicted response to immune checkpoint inhibitors in the first-line treatment of NSCLC (13,14). However, the relationship between TMB scores in tissue and blood remains unclear.…”
Section: What Is Tmb?mentioning
confidence: 99%
“…On the contrary, mutations of ARID1A, which belongs to the ARID1 family member, might be associated with a different outcome among patients received ICIs treatment and participate to the improved ICIs outcome in NSCLC via associating KRAS mutations as reported by Gandara D, et al Besides, Goswami S, et al con rmed that ARID1A mutations plus CXCL13 expression as combinatorial biomarkers to predict the sensitive phenotype to ICIs in metastatic urothelial carcinoma [30]. In addition, the NGS examination based on MYSTIC trial [31] revealed that ARID1A mutations are associated with improved outcomes with the PD-1 inhibitor durvalumab plus the CTLA4 inhibitor tremelimumab reported by Rizvi NA, et al Based on these studies for new biomarkers of cancer immunotherapy especially for ARID1A mutations, we conducted our research in order to further investigate the signi cance of ARID1 mutations, including ARID1A and ARID1B, in predicting the prognosis of ICIs treatment for advanced NSCLC.…”
Section: Discussionmentioning
confidence: 91%
“…The MYSTIC [26] trial is a phase III trial of patients with lung cancer that uses the same strategy but different drugs, such as Durvalumab (anti-PD-L1) and Tremelimumab (anti-CTLA-4) as rst-line therapy. This experiment included 1118 patients, and the median OS was 11.9 months (95% CI, 9.0-17.7) with Durvalumab plus Tremelimumab (HR vs. chemotherapy, 0.85; 98.77% CI, 0.61-1.17; P = 0.20).…”
Section: Discussionmentioning
confidence: 99%